Acta Biotheoretica Mathematical and philosophical foundations of biological and biomedical science - Jacobs, F.J.A.; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer.)
Acta Biotheoretica is devoted to the promotion of theoretical biology, encompassing mathematical biology and the philosophy of biology, paying special attention to the methodology of formation of biological theory. Papers on all kind of biological theories are welcome. Interesting subjects include philosophy of biology, biomathematics, computational biology, genetics, ecology and morphology. The process of theory formation can be presented in verbal or mathematical form. Moreover, purely methodological papers can be devoted to the historical origins of the philosophy underlying biological theories and concepts. Papers should contain clear statements of biological assumptions, and where applicable, a justification of their translation into mathematical form and a detailed discussion of the mathematical treatment. The connection to empirical data should be clarified. Acta Biotheoretica also welcomes critical book reviews, short comments on previous papers and short notes directing attention to interesting new theoretical ideas.
Keywords: Biology -- Philosophy; Evolutionary biology; Philosophy of Biology; Evolutionary Biology